2017
DOI: 10.1016/j.pbiomolbio.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-electrical feedback in the clinical setting: Current perspectives

Abstract: Mechano-electric feedback (MEF) is an established mechanism whereby myocardial deformation causes changes in cardiac electrophysiological parameters. Extensive animal, laboratory and theoretical investigation has demonstrated that abnormal patterns of cardiac strain can induce alteration of electrical excitation and recovery through MEF, which can potentially contribute to the establishment of dangerous arrhythmias. However, the clinical relevance of MEF in patients with heart disease remains to be established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 152 publications
0
36
0
Order By: Relevance
“…Although the main function of electrical excitation in the heart is to trigger mechanical contraction, the latter influences in turn electrical wave propagation via processes called mechano-calcium feedbacks (MCF) and mechano-electric feedbacks (MEF) [1][2][3]. Physiologically, mechanical conditions ensure the adaptation of the normal myocardium to varying external and internal mechanical conditions of contraction, including global and local mechanical loading and length Page 2 of 23 Balakina- Vikulova et al J Physiol Sci (2020) 70:12 duplexes, and one-dimensional models of heterogeneous cardiac tissue [5,6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the main function of electrical excitation in the heart is to trigger mechanical contraction, the latter influences in turn electrical wave propagation via processes called mechano-calcium feedbacks (MCF) and mechano-electric feedbacks (MEF) [1][2][3]. Physiologically, mechanical conditions ensure the adaptation of the normal myocardium to varying external and internal mechanical conditions of contraction, including global and local mechanical loading and length Page 2 of 23 Balakina- Vikulova et al J Physiol Sci (2020) 70:12 duplexes, and one-dimensional models of heterogeneous cardiac tissue [5,6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the pathological manifestations of these feedbacks can be quite dramatic: for example, they can cause heart rhythm disturbances and even lead to sudden cardiac death [1]. Experimental data on electromechanical activity are available mostly for animal hearts, while data for the human cardiomyocyte are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that MCF and MEF both for smaller afterloads as compared to bigger ones and for various mechanical interventions during isometric and isotonic twitches substantially affect durations of calcium transient and action potential in the human cardiomyocyte model. Although the main function of electrical excitation in the heart is to initiate mechanical contraction, mechanical contraction also affects electrical wave propagation via processes called mechano-calcium feedbacks (MCF) and mechano-electric feedbacks (MEF) [1][2][3]. Physiological role of the influence of mechanical conditions on the activity of the heart muscle is manifested, in particular, in adaptation of normal myocardium to varying external and internal mechanical conditions of contraction, including global and local mechanical loading and length redistribution between interacting heterogeneous cardiomyocytes in the heart chamber walls [4].…”
mentioning
confidence: 99%
“…On the other hand, the pathological manifestations of these feedbacks can be quite dramatic: for example, they can cause heart rhythm disturbances and even lead to sudden cardiac death [1]. The experimental data on the electromechanical activity are mainly collected in animal heart; however, data for the human cardiomyocyte are very limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation